2015
DOI: 10.1016/j.mayocp.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protocolized Sedation on Clinical Outcomes in Mechanically Ventilated Intensive Care Unit Patients

Abstract: In mechanically ventilated adults in closed, nonspecialty ICUs, protocolized sedation seems to decrease overall mortality (15%), ICU and hospital lengths of stay (1.73 and 3.55 days, respectively), and tracheostomy (31%) compared with usual care without protocolized sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 31 publications
3
36
1
3
Order By: Relevance
“…This included lung-protective mechanical ventilation with low tidal volumes,22 23 higher positive end-expiratory pressure levels24 in patients with more severe forms of ARDS and prone positioning 25. Furthermore, a restrictive fluid protocol was used,26 and analgo-sedation was performed using validated sedation scales preferring bolus versus continuous sedation 27…”
Section: Methodsmentioning
confidence: 99%
“…This included lung-protective mechanical ventilation with low tidal volumes,22 23 higher positive end-expiratory pressure levels24 in patients with more severe forms of ARDS and prone positioning 25. Furthermore, a restrictive fluid protocol was used,26 and analgo-sedation was performed using validated sedation scales preferring bolus versus continuous sedation 27…”
Section: Methodsmentioning
confidence: 99%
“…(4,5) Sedation protocols (25) and daily sedation interruption (8) have been studied for over 15 years and have shown significant benefits in terms of outcomes (10,11) and safety with respect to adverse events, such as accidental extubation, extubation failure (9,25) and long-term psychological outcomes. (12) The results of our meta-analysis do not suggest significant differences between the two approaches in regard to important outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…(10) The second systematic review included only randomized studies and pooled their results into a meta-analysis, which indicated that there were reduced ICU and hospital length of stay and reduced mortality with the use of both sedation reduction strategies. (11) Another meta-analysis also suggested that the two sedation minimization strategies were not associated with higher incidences of post-traumatic stress in the long term, (12) which was a fear that had been raised when the first study on daily sedation interruption was published. (13) …”
Section: Introductionmentioning
confidence: 99%
“…The need for sedation should be assessed regularly and sedative doses adjusted accordingly, with the aim of withdrawing sedatives completely as soon as possible. Sedative protocols may be of use (34), but most studies assessing protocolized sedation were conducted using benzodiazepines and there are few studies that have assessed this strategy in ICUs that use minimal sedation. Figure 1.…”
Section: Adequate Analgesiamentioning
confidence: 99%